Framing analysis of government crisis communication in terrorist attacks (Case in New Zealand and Sri Lanka) - Prastya, Narayana Mahendra; Dewi, Mutia (Informasi, 2020)
This article aims to analyze the frame of the government official statement in Mosque Christhurch Attack in New Zealand (March 2019) and Easter Sunday Attack in Sri Lanka (April 2019). The two cases were chosen because they place Muslim in contradictory positions: as victim in New Zealand and as perpetrator in Sri Lanka. This study uses framing analysis method to examine the official statement uploaded in the official websites of the Ministry of Foreign Affairs of New Zealand and the Ministry of Foreign Affairs of Sri Lanka, within seven days after the incident. The data gathered from the text analysis is then followed by data triangulation using expert judgement technique. The result shows that there are differences in information content. The New Zealand government emphasizes their own actions in the country, while the Sri Lankan government focuses on the activities carried out abroad and the supports, they receive from other countries. In doing so, the New Zealand government highlights the presence of Prime Minister Jacinda Ardern while the Sri Lankan government presents information from many state officials, instead of the head of state. These differences show that the content of official statement is highly influenced by the socio-political condition in the country.